The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1021/ol100331h
|View full text |Cite
|
Sign up to set email alerts
|

Cationic Pd(II)-Catalyzed Fujiwara−Moritani Reactions at Room Temperature in Water

Abstract: PdII-catalyzed Fujiwara-Moritani reactions can be carried out without external acid at room temperature, and in water as the only medium. A highly active cationic PdII catalyst, [Pd(MeCN)4](BF4)2, easily activates aromatic C-H bonds to produce electron-rich cinnamates in good yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
62
0
10

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 190 publications
(72 citation statements)
references
References 54 publications
(31 reference statements)
0
62
0
10
Order By: Relevance
“…Precedent for the catalytic alkenylation of C(sp 3 ) À H bonds is scarce; in most examples, simple acrylate or monosubstituted vinyl halides have been used. [17] We were pleased to find that the alkenylation of 1 with various disubstituted cyclic vinyl iodides provided the desired alkenylated product in moderate to good yields at slightly elevated temperatures (vinyl iodide (1.5 equiv), Pd(OAc) 2 (0.1 equiv), and AgOAc (1.5 equiv) in tBuOH at 110 8C). Interestingly, the ring size of the cyclic vinyl iodide had a strong influence on the reaction yield; the seven-membered iodide gave the highest yield (69 % yield of the isolated product 34).…”
Section: Methodsmentioning
confidence: 99%
“…Precedent for the catalytic alkenylation of C(sp 3 ) À H bonds is scarce; in most examples, simple acrylate or monosubstituted vinyl halides have been used. [17] We were pleased to find that the alkenylation of 1 with various disubstituted cyclic vinyl iodides provided the desired alkenylated product in moderate to good yields at slightly elevated temperatures (vinyl iodide (1.5 equiv), Pd(OAc) 2 (0.1 equiv), and AgOAc (1.5 equiv) in tBuOH at 110 8C). Interestingly, the ring size of the cyclic vinyl iodide had a strong influence on the reaction yield; the seven-membered iodide gave the highest yield (69 % yield of the isolated product 34).…”
Section: Methodsmentioning
confidence: 99%
“…44 Alternatively, it has been shown that Fujiwara–Moritani coupling reactions with acrylates can be carried out in PTS–water (eq 12) 45 by using a cationic source of palladium, as in commercially available [Pd(MeCN) 4 ](BF 4 ) 2 , 46 Both benzoquinone (1 equiv) and AgNO 3 (2 equiv) are required. Double functionalization ortho to the amide directing group is not observed here as well.…”
Section: Chemistry In Pts-h2o An Update: a 1st-generation Amphiphmentioning
confidence: 99%
“…The Palladium is probably inserted at the alpha position of olefin (COOH attached carbon) which exclusively leads to 3-substituted indoles exhibiting high regioselectivity. [17] Based on the existing literature, [18][19][20][21] and isolation of product; a plausible mechanism involving palladium catalytic cycle is outlined in Figure 2. The reaction is assumed to proceed via ortho-palladation of the anilide 1 giving intermediates I and II in succession.…”
mentioning
confidence: 99%